Factors influencing the success of targeted weight loss in healthcare providers with overweight and obesity after a six-month weight reduction intervention program - Siti Fatimah Samsury; Mohd Nazri Shafei; Mohd Ismail Ibrahim; Wan Nor Arifin Wan Mansor; Noriah Mahmud (PLoS ONE, 2025)
Obesity among healthcare providers (HCPs) affects their health and ability to provide care. In Terengganu, Malaysia, where 34% of adults are obese and over 50% of the workforce is overweight, targeted interventions are needed. Despite the importance of weight management in healthcare professionals, there is a lack of research focusing on effective strategies within this specific population. The study was conducted to identify factors associated with the success of targeted weight loss in HCPs with overweight and obesity following a six-month weight reduction intervention program. A cohort study involving HCPs with a body mass index (BMI) of 25 kg/m2 or higher was conducted in Terengganu, Malaysia, spanning from March to October 2023. All participants were required to undergo a six-month weight reduction intervention program. A participant who achieved a weight reduction of ≥ 5.0% during the follow-up period was considered successful in reaching the targeted weight reduction. Multiple logistic regression was applied to determine the factors associated with the success in achieving the targeted weight reduction. We found that the proportion of successfully achieved targeted weight reduction was 26.0%. The factors that were associated with the success of targeted weight reduction among HCPs with overweight and obesity were income (Adjusted Odds Ratio [AOR]: 0.94; 95% Confidence Interval [CI]: 0.88, 1.00, p-value 0.039), number of programs attended (AOR: 1.34; 95% CI: 1.02, 1.75, p-value 0.035), and the frequency of calorie intake recorded (AOR: 1.05; 95% CI: 1.02, 1.08, p-value 0.001). In conclusion, the proportion of successfully achieved targeted weight reduction was relatively low. To address this issue, future interventions need to concentrate on reinforcing participant self-monitoring and commitment levels. By emphasizing active progress tracking and cultivating strong dedication to the program’s objectives, there is a potential for significant improvements in weight management outcomes.